PELATIHAN LITERASI DIGITAL DI SMAN 15 SERAM BAGIAN BARAT - Zahrah, Nabila Anilda; Wahyudi, Rizqi (LPPM Universitas Nusa Mandiri, 2025)
Latu Village in West Seram faces challenges in accessing quality education, particularly in digital literacy. To address this issue, digital literacy training at SMAN 15 West Seram was implemented as a concrete step. The activity aims to enhance the digital understanding and skills of teachers and students so they can optimally utilize technology in the learning process. The training was held on August 21, 2024, from 09:00 to 12:00, using a training approach that included needs assessment, digital literacy socialization, discussions, and evaluation. The training materials covered basic software such as Microsoft Office and various online learning platforms. The results showed a significant increase in students’ knowledge of digital literacy, including internet safety, hoax identification, and the importance of verifying information. A total of 86.7% of students better understood the meaning of digital literacy, 96.7% became aware of its positive impact, and 93.3% knew how to respond to messages from strangers on social media, reflecting greater awareness of cybersecurity. Although the program successfully improved students’ skills and awareness, it still faced challenges such as limited internet access and inadequate school facilities. Nevertheless, this initiative is expected to serve as a model for developing education in remote areas and contribute meaningfully to improving the quality of education in Indonesia.